Training to Deliver Integrated Care Skills Aimed at the Future of Healthcare (Springer International Publishing, 2018)
This unique trainer's resource offers a comprehensive blueprint for preparing clinicians for practice in the changing and challenging environment of integrated care. Based firmly in new evidence-based models of behavioral care in medicine, it sets out the aims and objectives of modern integrated care delivery in a streamlined pedagogy-to-practice framework. Teaching strategies for developing core skills and competencies, suitable across diverse educational and workforce development settings, are presented with data-based rationales and guidelines for design and implementation. Chapters also cover the range of essentials, from research support to business acumen to program evaluation methods, needed to meet bedrock goals of improved quality of care, clinical outcomes, and patient satisfaction. The book's comprehensive coverage: Reviews the evidence base for integrating medical and behavioral care. Provides empirically sound guidelines for training learners in integrated practice. Breaks down skill development into critical training objectives. Offers detailed content of a current degree program in integrative behavioral medicine. Recommends measures to support responsive, patient-centered, and sustainable training programs. A robust guide to a more inclusive and effective future, Training to Deliver Integrated Care expands the healthcare horizon to accommodate trainers working in health psychology, general practice, primary care medicine, and consulting, as well as supervision and coaching professionals.